Biomechanical contributions of upper cervical ligamentous structures in Type II odontoid fractures. (23rd January 2019) - Tisherman, Robert; Vaudreuil, Nicholas; Ramanathan, Rahul; Hartman, Robert; Lee, Joon; Bell, Kevin
Abstract: Fractures of the odontoid present frequently in spinal trauma, and Type II odontoid fractures, occurring at the junction of the odontoid process and C2 vertebrae, represent the bulk of all traumatic odontoid fractures. It is currently unclear what soft-tissue stabilizers contribute to upper cervical motion in the setting of a Type II odontoid fracture, and evaluation of how concomitant injury contributes to cervical stability may inform surgical decision-making as well as allow for the creation of future, accurate, biomechanical models of the upper cervical spine. The objective of the current study was to determine the contribution of soft-tissue stabilizers in the upper cervical spine following a Type II odontoid fracture. Eight cadaveric C0-C2 specimens were evaluated using a robotic testing system with motion tracking. The unilateral facet capsule (UFC) and anterior longitudinal ligament (ALL) were serially resected to determine their biomechanical role following odontoid fracture. Range of motion (ROM) and moment at the end of intact specimen replay were the primary outcomes. We determined that fracture of the odontoid significantly increases motion and decreases resistance to intact motion for flexion–extension (FE), axial rotation (AR), and lateral bending (LB). Injury to the UFC increased AR by 3.2° and FE by 3.2°. ALL resection did not significantly increase ROM or decrease end-point moment. The UFC was determined to contribute to 19% of intact flexion resistance and 24% of intact AR resistance. Overall, we determined that Type II fracture of the odontoid is a significant biomechanical destabilizer and that concurrent injury to the UFC further increases upper cervical ROM and decreases resistance to motion in a cadaveric model of traumatic Type II odontoid fractures.